Subjective Sleep Measures in Children: Self-Report - Erwin, Andrea M.; Bashore, Lisa (Frontiers in Pediatrics, 2017)
The American Academy of Sleep Medicine (AASM) recently published a consensus statement on the recommended number of hours of sleep in infants and children. The AASM expert panel identified seven health categories in children influenced by sleep duration, a component of sleep quality. For optimal health and general function, children require a certain number of hours of sleep each night. Limited data exists to subjectively assess sleep in this population. Practitioners must evaluate overall sleep quality not simply sleep duration. The purpose of this article is to provide a mini review of the self-report sleep measures used in children. The authors individually completed a review of the literature for this article via an independent review followed by collaborative discussion. The subjective measures included in this mini review have been used in children but not all measures have reported psychometrics. Several tools included in this mini review measure subjective sleep in children but with limited reliabilities or only preliminary psychometrics. Accurate measurement of self-reported sleep in children is critical to identify sleep problems in this population and further detect associated health problems. Ongoing studies are warranted to establish reliable and valid measures of self-reported sleep in children to accurately detect health problems associated with poor sleep quality. This mini review of the literature is an important first step to identify the most reliable subjective sleep measures in children.